A GIS-based index tool for the selection of ponds for fisheries - Khanna, Chitra (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Central India, a GIS-based geo-hydrological composite index tool has been developed to enable the selection of suitable perennial ponds for fisheries. The tool also allows users to take a comprehensive view of a district and make decisions for natural resource management interventions.